Thermal dissociation of multimeric protein complexes by using nanoelectrospray mass spectrometry. - Benesch, J; Sobott, F; Robinson, C (2003)
The behavior of macromolecular systems at different temperatures is often crucial to their biological activity and function. While heat-induced changes of individual proteins are readily monitored by a number of spectroscopic methods, changes in noncovalent complexes of biomolecules are more challenging to interpret. Nanoelectrospray mass spectrometry is becoming increasingly powerful in the study of large noncovalent complexes, and here we describe the design, characterization, and application of a novel probe that allows the thermocontrol of the solution in the electrospray capillary. The transition temperature for the unfolding of the protein lysozyme is readily obtained and correlates closely with that measured by fluorescence spectroscopy, thereby demonstrating the validity of this approach. We apply this technique to the study of the 200-kDa complex of the small heat shock protein TaHSP16.9, revealing both its dissociation into suboligomeric species and an increase in its size and polydispersity at elevated temperatures. In contrast, gas-phase activation of this complex is also carried out and yields a dissociation pathway fundamentally different from that observed for thermal activation in solution. As such, this probe allows the study of the reversible heat-induced changes of noncovalent complexes in a biologically relevant manner.